Stalinist plan: A challenge to public administration in universities - Khanyile, M. (South African Journal of Higher Education, 2025)
Universities face the challenges of substantial reforms such as new managerialism, corporatism, neoliberalism, McDonaldisation, entrepreneurialism, massification, decolonisation, and many other approaches, philosophies, and practices that influence the original idea of the university. In competitive environments, new managerialism in the public sector can be a means of achieving more efficient, flexible, and adaptable management, thus, the permeation and manifestation of new managerialism in public higher education engender business practices and private‒sector ideas. Furthermore, these transformations include globalisation and internationalisation, mass participation and vocational credentialing; business‒like administration and internal product and performance regimes; quasi‒market competition between institutions; and the part marketisation of teaching and research and services. These managerialist ideas, embedded in a neo‒liberal conception of globalisation, have specific implications for higher education in the sense that they have the potential to limit contribution to future public administration research and graduate products to serve as public servants. Compounding the situation is academic capitalism, academic entrepreneurs, entrepreneurial academics and the commodification and commoditisation of a public good (education). Furthermore, even research universities seem to be giving way to entrepreneurial universities and are associated with the emergence of corporate universities. The university’s entrepreneurial behaviour is seen in professors’ perspectives on the university’s role in knowledge dissemination ‒ innovation agents being entrepreneurial academics and academic entrepreneurs ‒ the former resembles innovative university members, while the latter resembles a typical start‒up entrepreneur. This “Stalinist plan or new managerialism or new functionalism” and entrepreneurialism represents a healthy capitalist enterprise and propel thinking about whether or not universities pursue epistemologies, ontological scholarship, research and curriculum to improve public administration. This conceptual paper identifies complexities in propelling universities to a higher fitness landscape in producing public administration research and graduates. This is because a public university now fends for itself as it influences distinctive segments of the economy and militates against origins of public administration.